2021
DOI: 10.1038/s41598-021-03053-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macular fluid features on outcomes of anti-vascular endothelial growth factor treatment for type 3 macular neovascularization

Abstract: We evaluated the impact of macular fluid features on visual and anatomical outcomes in type 3 macular neovascularization (MNV) patients treated with anti-vascular endothelial growth factor (VEGF). We retrospectively enrolled 89 eyes with type 3 MNV with at least 12 months of follow-up. All patients were treatment-naïve and received a monthly loading injection of anti-VEGF for three months, followed by further injections as required. The association of baseline macular morphology, including intraretinal fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…(Daniel et al, 2017, Sharma et al, 2016, SriniVas et al, 2018 Recently, it has been shown that this association between fluid location and visual outcome is strictly dependent on the type of NVM. (Sharma et al, 2022;Yoon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(Daniel et al, 2017, Sharma et al, 2016, SriniVas et al, 2018 Recently, it has been shown that this association between fluid location and visual outcome is strictly dependent on the type of NVM. (Sharma et al, 2022;Yoon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%